Study on Marketing & Accessibility of Horticultural Crops-Eastern Himalayan Region (Zone-II) - Planning Commission (Planning Commission, 1989)
The Planning Commission is in the process of preparing agricultural development plans based on the concept of Agro-climatic heterogeneity and accordingly, the country has been divided into 15 Agro-climatic zones. The Eastern Himalayan Region which is one of these comprise of the States of Assam, Arunachal Pradesh, Meghalaya, Manipur, Mizoram, Tripura, Nagaland and Sikkim and three districts of West Bengal (Darjeeling, Jalpaiguri and Cooch Behar).
Planning Commission Agro-Climatic Regional Planning Unit
Operations Research Group